Manubiae, praedae i spolia - określenia rzymskiej zdobyczy wojennej - Jarych, Adam Jakub (Studia Europaea Gnesnensia, 2016)
In this paper the reader is acquainted with the most important issues associated with the proceeds of Roman plunder and pillage, to which the sources refers as manubiae, praeda and spólia. The deliberations are based on numerous narrative and epigraphic accounts, presenting the manner in which spoils of war were distributed by the leaders of the Re-publican period.